Reading and teaching ancient fiction: Jewish, Christian, and Greco-Roman narratives - Johnson, Sara Raup; Dupertuis, Rubén R.; Shea, Christine Rita (Writings from the Greco-Roman world / Supplement, 2018)
"The essays in this volume explore facets of ongoing research into the interplay of history, fiction, and narrative in ancient Greco-Roman, Jewish, and Christian texts. Particular attention is given to the way in which ancient authors in a variety of genre and cultural settings employ a range of narrative strategies to reflect on pressing contemporary issues, shape community identity, or provide moral and educational guidance for their readers. This volume, the third in a series of volumes of collected papers emerging from the work of the "Ancient Fictions and Early Christian and Jewish Narrative" section of the Society for Biblical Literature since its formation in 1992, is the first to highlight the growing importance of strategies to integrate the fruits of this research into the university classroom and beyond" --